2017
DOI: 10.1159/000480416
|View full text |Cite|
|
Sign up to set email alerts
|

Globular Adiponectin Attenuated H2O2-Induced Apoptosis in Rat Chondrocytes by Inducing Autophagy Through the AMPK/ mTOR Pathway

Abstract: Background/Aims: Chondrocyte apoptosis is closely related to the development and progression of osteoarthritis. Global adiponectin (gAPN), secreted from adipose tissue, possesses potent anti-inflammatory and antiapoptotic properties in various cell types. This study aimed to investigate the role of autophagy induced by gAPN in the suppression of H 2 O 2 -induced apoptosis and the potential mechanism of gAPN-induced autophagy in chondrocytes. Methods: H 2 O 2 was used to induce apoptotic injury in rat chondrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 62 publications
(57 reference statements)
1
36
0
Order By: Relevance
“…Globular adiponectin suppressed LPS-primed inflammasome activation by stimulating AMPK signaling pathways [140]. Additionally, rat chondrocyte was protected from apoptosis by globular adiponectin-induced AMPK-mTOR signaling [141].…”
Section: Globular Adiponectin With a Pro-inflammatory Effectmentioning
confidence: 96%
“…Globular adiponectin suppressed LPS-primed inflammasome activation by stimulating AMPK signaling pathways [140]. Additionally, rat chondrocyte was protected from apoptosis by globular adiponectin-induced AMPK-mTOR signaling [141].…”
Section: Globular Adiponectin With a Pro-inflammatory Effectmentioning
confidence: 96%
“…Chondrocyte apoptosis is closely related to the development and progression of osteoarthritis. A previous study has demonstrated that H 2 O 2 can induce chondrocytes apoptosis and caspase-3 activation in rat chondrocytes [ 43 ]. In the study, both HA and CeO 2 nanoparticles could lower chondrocytes apoptosis induced by H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of studies have revealed that ROS was involved in the apoptosis related to these conditions [40,41]. Other researchers have also demonstrated that low concentrations of H 2 O 2 can induce apoptosis in a variety of cells [42,43]. In addition, research has also found that dexmedetomidine exhibits an anti-oxidative stress effect by significantly inhibiting the excessive production of ROS.…”
Section: Discussionmentioning
confidence: 99%